2015
DOI: 10.1007/s11104-015-2463-z
|View full text |Cite
|
Sign up to set email alerts
|

Root carbon inputs under moderately diverse sward and conventional ryegrass-clover pasture: implications for soil carbon sequestration

Abstract: Background and aims A strategy to increase soil C under pasture-based systems is to increase the root mass inputs or increase rooting depth of plants. Our objective in this study was to measure the seasonal dynamics of root mass and C inputs under two different pasture types (ryegrass-clover vs moderately diverse) that differ in plant diversity and which are commonly used in New Zealand agriculture. Methods This study was carried out on an existing plant diversity field trial containing six replicate paddocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 52 publications
(55 reference statements)
3
40
0
Order By: Relevance
“…However, the SO 13 C content (Fig. 3) depends mainly on plant biomass (McNally et al 2015). In our study, there was a significant positive correlation between the SO 13 C content and root biomass (Fig.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…However, the SO 13 C content (Fig. 3) depends mainly on plant biomass (McNally et al 2015). In our study, there was a significant positive correlation between the SO 13 C content and root biomass (Fig.…”
supporting
confidence: 61%
“…2c) and SO 13 C content (Fig. 3) from end 6-h to the final day further indicates that substantial photosynthetically-fixed C enters the SOC pools (Pausch et al 2013;McNally et al 2015), but microbial respiration can decrease the actual amount of SO 13 C deposited (Bahn et al 2009;Kuzyakov and Gavrichkova 2010).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…While a slight decreased of SOC content was found in 20-year restoration land, the trend was consist with the changed of biomass. Because plant roots made significant contributions to soil carbon under grassland (McNally et al, 2015). Lv and Liang (2012) also found that during forest restoration, SOC did not consistently increase linearly with restoration years.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, changes in land use and management practices that affect soil respiration rates can have a significant impact on atmospheric CO2 concentrations and soil C pools (McNally et al 2015). In the United States, agriculture alone occupies 51.3% (1.16 billion acres) of the total land area (Nickerson et al 2011) and is among the largest net sources of atmospheric C resulting from land use change (US EPA 2004).…”
Section: Introductionmentioning
confidence: 99%